Municipalização da gestão ambiental: situação atual dos municípios do Estado do Pará - TOZI, Shirley Capela (Universidade Federal do Pará, 2014)
The object of the present work happens only on the analysis of the structures of environmental management in the State of the Pará. Whose principal objective is to analyse and to value the municipalization of the environmental management in the State of the Pará, without taking into account the real functioning of the environmental structures in the State. The local authority and the bigregions (a kind of regionalization) were chosen like the form of regionalization for checking of the effectiveness of the State Politics of Environment and of the municipalization of the environmental management. The State of the Pará was selected like area of study owing to the environmental problems and the preoccupation of the State in developing politics that fight the free past of the State with the environment: fiscal incentives and introduction of structures for projects of regional development that modified the environment, and local authorities of ancient and recent creation. By the way, which competences of the local authorities in the context of the corresponding legislation to environmental management? How is it taking place to the decentralization of the environmental management in the State of the Pará? What the current characteristics of the environment? For so much, it was used like methodology: bibliographical and documentary inquiry; and analysis of datas of the locals authorities, through the IBGE (Brazilian Institute of Geography and Statistic) and of the SECTAM (Executive General Office of Science, Technology and Environment). The importance of the developed subject reveals itself in the necessity of municipalizing the environmental management, in other words, in the change of posture of the state, before centralizated and authoritary, for a democratic posture, turning in the environmental and territorial management, that consists of another form of create, decid and execult public politics.